CRITICAL STATE SELECTION OF THE DYNAMIC HORIZONTAL IMPACT TEST FOR A CERTAIN TYPE AIRLINE SEAT INSTALLED - HUANG WanJia; HAN Liang (Jixie qiangdu)
According to the critical state selection issue of horizontal dynamic impact test in the pilot’s seat / restraint system for a certain type of general aviation aircraft. The critical state is selected through simulation analysis and test in the seat’s dynamic impact test,while the critical state is also validated by both simulation and test to ensure it can meet the safety requirements of airworthiness. The simulation analysis shows a consistency compared with the test on horizontal dynamic impact test,and this laid a foundation for future research works.